2023
DOI: 10.1523/jneurosci.1312-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Irreversibility of Large-Scale Brain Dynamics in Alzheimer’s Disease

Abstract: Healthy brain dynamics can be understood as the emergence of a complex system far from thermodynamic equilibrium. Brain dynamics are temporally irreversible and thus establish a preferred direction in time (i.e., arrow of time). However, little is known about how the time-reversal symmetry of spontaneous brain activity is affected by Alzheimer's disease (AD). We hypothesized that the level of irreversibility would be compromised in AD, signaling a fundamental shift in the collective properties of brain activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…Alzheimer’s disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are among the most prevalent neurodegenerative diseases, each linked to specific pathophysiology and to highly heterogeneous and atypical manifestation, hindering detection and diagnosis ( Musa et al, 2020 ; Parra et al, 2018 ). Neuroimaging methods such as positron emission tomography (PET) ( Engler et al, 2008 ; Foster et al, 2007 ; Jack et al, 2018 ; Mosconi et al, 2008 ; Nordberg, 2004 ), functional magnetic resonance imaging (fMRI) ( Hafkemeijer et al, 2015 ; Jalilianhasanpour et al, 2019 ; Moguilner et al, 2021 ), and electroencephalography (EEG) Dottori et al, 2017 ; Lindau et al, 2003 ; Nishida et al, 2013 ; Nishida et al, 2011 ; Cruzat et al, 2023 have been employed extensively to profile these diseases based on their underlying whole-brain activity patterns, and to develop automated classifiers capable of assisting clinical decision-making ( Kim et al, 2019 ; Moguilner et al, 2021 ; Herzog et al, 2022 ). In spite of these advances, the limited knowledge of the large-scale network mechanisms of neurodegenerative dementias hinders the development of interventions oriented to improve brain health and subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are among the most prevalent neurodegenerative diseases, each linked to specific pathophysiology and to highly heterogeneous and atypical manifestation, hindering detection and diagnosis ( Musa et al, 2020 ; Parra et al, 2018 ). Neuroimaging methods such as positron emission tomography (PET) ( Engler et al, 2008 ; Foster et al, 2007 ; Jack et al, 2018 ; Mosconi et al, 2008 ; Nordberg, 2004 ), functional magnetic resonance imaging (fMRI) ( Hafkemeijer et al, 2015 ; Jalilianhasanpour et al, 2019 ; Moguilner et al, 2021 ), and electroencephalography (EEG) Dottori et al, 2017 ; Lindau et al, 2003 ; Nishida et al, 2013 ; Nishida et al, 2011 ; Cruzat et al, 2023 have been employed extensively to profile these diseases based on their underlying whole-brain activity patterns, and to develop automated classifiers capable of assisting clinical decision-making ( Kim et al, 2019 ; Moguilner et al, 2021 ; Herzog et al, 2022 ). In spite of these advances, the limited knowledge of the large-scale network mechanisms of neurodegenerative dementias hinders the development of interventions oriented to improve brain health and subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Harnessing the principles of thermodynamics, we quantified hierarchy by computing the level of irreversibility in brain signals during resting state conditions. Specifically, we captured the level of irreversibility through entropy production 69,71,74,76,77 as computed through a sophisticated clustering strategy. Note that resting states cover a rich range of the dynamical repertoire of the brain and thus those are ideal to characterise the most general and wide variety of interaction across the whole brain, i.e., the underlying hierarchical orchestration.…”
Section: Discussionmentioning
confidence: 99%
“…Then the data was converted into Statistical Parametric Mapping (SPM) formatting and further pre-processed in MATLAB (MathWorks, Natick, MA, USA) using in-house-built codes (LBPD, available at https://github.com/leonardob92/LBPD-1.0.git) and the Oxford Centre for Human Brain Activity (OHBA) Software Library (OSL) (available at https://ohba-analysis.github.io/osl-docs/) [38]. OSL is freely available software that builds on the Fieldtrip [29], FSL [39], and SPM [12] toolboxes. Next the continuous MEG data was visually inspected and large artefacts were removed.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…This fundamental observation has prompted the development of a range of techniques to provide a measure for the degree of non-equilibrium in neuroimaging time-series recorded in different conditions [510]. These measures have shown that the degree of non-equilibrium is elevated during cognitive tasks [4–7] whilst reduced in both impairments of consciousness [11], sleep [10] and Alzheimer’s disease [12] indicating that non-equilibrium may be a key signature of healthy consciousness and cognition in the brain [13]. Despite this, current methods are restricted to aggregate measures of non-equilibrium.…”
Section: Introductionmentioning
confidence: 99%